Micro-mechanical model of vertebral trabecular bone with application in analysis of screw pull-out strength - Zhang, Qinghang (2008)
A nonlinear micro-mechanical model of the human vertebral trabecular bone using a three-dimensional open-celled regular hexagonal structure was developed. Anisotropy of the bone material properties was accounted for. Nonlinearity of the structure was introduced by considering the elasto-plastic behavior of each internal beam, from which the plastic stress-strain relation of the structure can be modeled by localized beam deformation. The results show that the three-dimensional regular hexagonal model can efficiently reflect the mechanical behavior of human vertebral trabecular bone. The predicted elastic modulus and yield stress in longitudinal loading direction are in agreement with published experimental data. The behavior of the trabecular bone varies when subjected to different loading and boundary conditions.